(untitled) (Revista de História da UEG (REVHIST), 2023)
The research work brings reflections on the Brazilian environmentalist movement and Environmental Education, through the historical trajectory that delineated the field of Environmental Education in Brazil until the present day. In this way, it is evident throughout the course of the world history of environmentalism that environmental activists have been waging incessant struggles that are the result of a crisis caused by the capitalist system. Therefore, it is from the 1970s that Environmental Education is conceptualized and becomes part of government proposals in several countries, especially in Brazil, with the institution of legislation and specific programs. However, in the years of former president Jair Messias Bolsonaro’s administration, the country underwent major political setbacks that vehemently affected socio-environmental issues. Keywords: Environmentalism. Environment. Education.